2011
DOI: 10.1177/1748895811401977
|View full text |Cite
|
Sign up to set email alerts
|

Beyond folk devil resistance: Linking moral panic and moral regulation

Abstract: This article is a contribution to widening the focus of moral panic studies. Our aim is to advance recent attempts to link moral panic studies to the criminological literature on moral regulation. We argue that moral panics should be conceptualized as volatile expressions of long-term moral regulation processes. To substantiate these conceptual and theoretical arguments, we examine claims-making activities about the threat posed by British youth who don hooded tops in public places.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…For example, Hier () initially conceptualized efforts to regulate rave dance parties in the City of Toronto in terms of a perceived breakdown in ongoing efforts to regulate youth leisure activities. Hier, Walby, Lett, and Smith () subsequently demonstrated how attempts to ban hooded tops from public locations in Britain derived from perceived breakdowns in the regulatory power of the Anti‐Social Behavior Act as a state mechanism of moral regulation. Lundström () applied the framework to claims about benefit fraud in Sweden, Siltaoja () to unethical business practices in Finland, Critcher () to anti‐doping policies in sport, Carlson () to radically motivated police violence and Smoczynski and Fitzgerald () to polish migrants in the UK.…”
Section: Moral Panic and Moral Regulationmentioning
confidence: 99%
“…For example, Hier () initially conceptualized efforts to regulate rave dance parties in the City of Toronto in terms of a perceived breakdown in ongoing efforts to regulate youth leisure activities. Hier, Walby, Lett, and Smith () subsequently demonstrated how attempts to ban hooded tops from public locations in Britain derived from perceived breakdowns in the regulatory power of the Anti‐Social Behavior Act as a state mechanism of moral regulation. Lundström () applied the framework to claims about benefit fraud in Sweden, Siltaoja () to unethical business practices in Finland, Critcher () to anti‐doping policies in sport, Carlson () to radically motivated police violence and Smoczynski and Fitzgerald () to polish migrants in the UK.…”
Section: Moral Panic and Moral Regulationmentioning
confidence: 99%
“…By characterizing moral panics as irrational, proponents of these contentions are unable to explain situations where threats have been consciously orchestrated and employed as discursive devices to generate moral panics in pursuit of specific political aims. Some authors have demonstrated that far from being irrational, episodic, and fleeting phenomena, moral panics are, in fact, part of the repertoire of governmentality (Hier, ; Hier, Lett, Walby, & Smith, ). Panics seek to organize behaviors and attitudes to conform to particular regimes of moral regulation.…”
Section: Moral Panics: a Critical Interrogationmentioning
confidence: 99%
“…The above image not only encapsulates the alleged destructive connotations and debauchery that are associated with homosexuality, but also embeds an urgent need for practices and programs that will ensure moral restoration. As Hier et al (, p. 260) point out:
Every moral panic has its folk devil: the personification of evil … When folk devils are revealed to the public in a stereotypical fashion through mainstream media reporting, they are constructed as threats to the social/moral fabric requiring immediate regulatory intervention.
…”
Section: Media Frames Expert Opinion and Pathologization Of Homosexmentioning
confidence: 99%
“…For example, when a moral panic about British youth who don hooded tops in public places developed in 2005, claims making activities centered on the dangers that hooded youth pose to otherwise ordinary Britons in public places. As Hier, Lett, Walby, and Smith (2011) explain, the panic emerged when existing state and extra‐state moral regulation processes (e.g., ASBOs, ABCs, codes of respect) were perceived to be in a state of failure. Through these processes, routine discourses that call upon individuals to engage in responsible forms of self‐conduct to manage risk were transposed into collectivizing discourses of risk management.…”
Section: Moral Regulation and Moral Panicmentioning
confidence: 99%